Speech of Joseph Hume, Esq. in the House of Commons, Thursday, July 25, 1822, on the national debt and the operation of the sinking fund (Hansard, 1822)
From Hansard's Parliamentary Debates, New Series; vol. VII, p. 1740. - The text is a report of the speech. - Pamphlet volume.